A fiscal outlook for Poland using generational accounts - Janusz Jabłonowski; Christoph Müller; Bernd Raffelhüschen (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2010)
During the next few decades the populations of most developed countries will grow older and older as a result of the low fertility rates since the 1970s and/or the continuously increasing life expectancy. Poland, one of the biggest countries in Central Europe, will be confronted rather seriously by this development. Generational Accounting which was introduced in the early nineties, can illustrate the effects of this ageing process on a country's fiscal situation. We show that the demographic development produces a major problem for the long term stability of Polish public finances. In particular the healthcare system deserves special attention for policy makers in the medium and long run, whilst the general pension system shall stabilise in the long term.
Keywords: H50; H55; H60; H68; J10; H30; 330; Generational Accounting; Fiscal sustainability; Fiscal policy; Poland; Pension reform